Correction coefficients for calculating the Young's modulus from the resonant flexural vibration - Štubňa, Igor (Strojniški vestnik, 2006)
A simple formula derived from the simplified differential equation of flexural vibration of a sample with a uniform cross-section does not give exact values for the Young's modulus or the velocity of sound if the ratio of the length to the diameter (or the length to the thickness) of the sample is less than 20. The error can be eliminated by multiplying the measured resonant frequency or the calculated Young's modulus by a correction coefficient. Some formulae for the correction coefficients as well as a new formula are presented and compared with the ASTM formulae.
Keywords: upogibno nihanje; resonančne frekvence; Youngov modul